Depolymerization of Poly(phosphinoboranes): From Polymers to Lewis Base Stabilized Monomers. Issue 2 (6th December 2017) - Marquardt, Christian; Hegen, Oliver; Vogel, Ariane; Stauber, Andreas; Bodensteiner, Michael; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract: We report on depolymerization reactions of poly(phosphinoboranes). The cleavage of the polymers [H2 PBH2 ] n (2 a ), [ t BuHPBH2 ] n (2 c ), [PhHPBH2 ] n (2 e ) and the oligomer [Ph2 PBH2 ] n (2 b ), with strong Lewis bases (LBs), in particular with NHCs, leads to the corresponding monomeric phosphanylboranes R 1 R 2 PBH2 LB. It is observed that the depolymerization depends on the strength and stability of the LBs as well as on the substitution pattern of the poly(phosphinoboranes). The solid state structures of the monomeric phosphinoboranes H2 PBH2 NHC Me (NHC=N‐heterocyclic carbene) (4 a ), H2 PBH2 NHC dipp (5 a ) and t BuHPBH2 NHC Me (4 c ) were determined. DFT calculations support the experimentally observed reaction behavior. Abstract : Back to the monomers ! A recycling strategy for high molecular weight poly(phosphinoboranes) by depolymerization with strong Lewis bases was discovered. N‐heterocyclic carbenes proved to be a valuable tool for these cleavage reactions.